Classificação e composição química dos grãos de soja cultivados na Região Oeste do Paraná - Tomasi, Graziele Afonso (2024)
Brazil has stood out in the production and marketing of grains, reinforcing the importance of agricultural activities for the country's economy. Soy is the main Brazilian agricultural crop, with the country leading the world in the production and export of this grain, and Paraná is among the main producers. The commercialization of products of plant origin, such as soybeans, is based on the qualitative aspects of the product, categorized into Group, Class, and Type of grains, evaluated according to standards that follow legislation regulated by the Ministry of Agriculture, Livestock and Supply (MAPA). Considering the expansion of this sector, this work seeks to evaluate the classification of soybeans received in a storage unit in the Western Region of Paraná between the years 2010 and 2024 and the chemical quality, as well as classification in the 2022/2023 harvest. To this end, the classification of grains was carried out and assessed, and the oil, protein, fiber and water content was measured, correlating with MAPA's public consultation ordinance no. 532 to evaluate new classification standards based on the export market. The data was evaluated through the average of agricultural harvests for water content, impurities and damage, correlating the harvests with the classification standards. Data from the 2022/2023 harvest were evaluated using infrared spectrometry (NIR), correlating the levels with public consultation standards. The results indicate a fluctuation in water content from 15.26 to 19.76%, and an increase in the content of impurities in the grains, as well as an increase in the number of loads received at the company in the last fourteen years. Rainfall becomes harmful when its volume increases during the harvest period, as observed in the 2022/2023 harvest, with a higher rate of damaged grains. The results showed a negative correlation between oil and protein content. The grains produced in the Western region of Paraná do not fit into Group III of the new classification proposal, ordinance no.532/2022, as they do not meet minimum standards of 40% protein and 20% oil. There is a need for genetic changes to meet the demands of export trade and the importance of measuring protein and oil in grains at the time of receiving in storage units, according to the destination for marketing the commodity, is evident.